New Cases of Maleylacetoacetate Isomerase Deficiency with Detection by Newborn Screening and Natural History over 32 Years: Experience from a German Newborn Screening Center - Gwendolyn Gramer; Saskia B. Wortmann; Junmin Fang-Hoffmann; Dirk Kohlmüller; Jürgen G. Okun; Holger Prokisch; Thomas Meitinger; Georg F. Hoffmann (MDPI AG, 2024)
Newborn screening (NBS) for hepatorenal tyrosinemia type I (HT1) based on a determination of succinylacetone is performed in countries worldwide. Recently, biallelic pathogenic variants in GSTZ1 underlying maleylacetoacetate isomerase (MAAI) deficiency have been described as a differential diagnosis in individuals with slightly elevated succinylacetone detected by NBS. We report the experience with NBS for HT1 over 53 months in a large German NBS center and the identification and characterization of additional cases with MAAI deficiency, including one individual with a natural history over 32 years. A total of 516,803 children underwent NBS for HT1 at the NBS center in Heidelberg between August 2016 and December 2020. Of 42 children with elevated succinylacetone, HT1 was confirmed in two cases (1 in 258.401). MAAI deficiency was suspected in two cases and genetically confirmed in one who showed traces of succinylacetone in urine. A previously unreported pathogenic GSTZ1 variant was found in the index in a biallelic state. Segregation analysis revealed monoallelic carriership in the index case's mother and homozygosity in his father. The 32-year-old father had no medical concerns up to that point and the laboratory work-up was unremarkable. MAAI has to be considered a rare differential diagnosis in NBS for HT1 in cases with slight elevations of succinylacetone to allow for correct counselling and treatment decisions. Our observation of natural history over 32 years adds evidence for a benign clinical course of MAAI deficiency without specific treatment.